Winter of the world - Follett, Ken. frey50 (New York : Dutton, 2012)
This novel continues the stories of five interrelated families who struggle with social, political, and economic turmoil in the mid-twentieth century, during which they witness the rise of Nazi Germany, the Spanish Civil War, and the horrors of World War II. It picks up right where the first book left off, and continues up to the explosions of the American and Soviet atomic bombs. Carla von Ulrich, born of German and English parents, finds her life engulfed by the Nazi tide until she commits a deed of great courage and heartbreak.. American brothers Woody and Chuck Dewar, each with a secret, take separate paths to momentous events, one in Washington, the other in the bloody jungles of the Pacific. English student Lloyd Williams discovers in the crucible of the Spanish Civil War that he must fight Communism just as hard as Fascism. Daisy Peshkov, a driven American social climber, cares only for popularity and the fast set, until the war transforms her life, not just once but twice, while her cousin Volodya carves out a position in Soviet intelligence that will affect not only this war, but the war to come. These characters and many others find their lives inextricably entangled as their experiences illuminate the cataclysms that marked the century. From the drawing rooms of the rich to the blood and smoke of battle, their lives intertwine, propelling the reader into dramas of ever increasing complexity.
Keywords: Twentieth century; Twentieth century -- History; Twentieth century -- Civilization; World War, 1939-1945; Europe -- History -- 20th century; United States -- History -- 20th century; Spain -- History -- Civil War, 1936-1939; Historical fiction; War stories; Domestic fiction